A new ethos for science? Exploring emerging DIY science "qualities". (January 2021) - Ferretti, Federico; Pereira, Ângela Guimarães
Highlights: By adopting the theory of Post Normal Science, DIY science can be studied as an 'extended peer community' performing processes of 'extended peer review'. Quality assurance in DIY science loses its normative and standardized aspects; DIY science participants engage in practices of extended peer review that are conceptualized as processes of quality maintenance. The DIY science is characterized by multiple 'qualities': care, agency, time, integrity and openness (ACTION). Mainstream science can take inspiration from the case of DIY science in the attempt to solve some of its internal tensions about quality. Abstract: This paper investigates the issue of quality in the context of DIY science, a consolidating ensemble of social practices progressively gaining attention also in academia and policy. Although rarely from official institutions and with formal affiliations, DIY science practitioners often perform scientific activity aimed at the solution of incumbent problems. What becomes of scientific quality in the DIY milieu? Departing from a Post Normal Science framework, we make the case of the DIY science community as an "extended peer community" performing practices of "extended peer review". Three real cases of DIY science suggest a preliminary set of quality dimensions intrinsic to the DIY practice. Subsequently, through a purposefully designed interview study with members of different DIY communities, we look further into these quality dimensions (or "qualities") and propose a possible "DIY ethos" embedding elements of agency, care, 'tempo', integrity and openness. DIY science practitioners are not necessarily concerned with quality assessments, but are rather engaged in the production of 'extended facts' that can be regarded in themselves as quality commitments, i.e. by acting, tinkering and hacking in the matters that are of their care and concern. We conclude by discussing that DIY science can also constitute a real case example to contrast currently existing tensions about the issue of quality in mainstream science.